1994
DOI: 10.1073/pnas.91.24.11636
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of intercalated four-stranded d(C3T) at 1.4 A resolution.

Abstract: The crystal structure of d(C3T), solved at 1.4 A resolution, reveals that the molecule forms a four-stranded intercalated complex. It consists of two parallel-stranded duplexes, each of which Is held together by cytosine-protonated cytosine base pairs. The two duplexes are intercalated with each other and have opposite strand orientation. The molecule has a flat, lath-like appearance, and the covalently bonded cytosines have a slow right-handed twist of 17.1°. However, there is considerable asymmetry. On one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
141
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 12 publications
7
141
1
Order By: Relevance
“…Backbone torsion angles (°) for selected nucleotides in the present structure Boldface type indicates values of torsions ␣ and ␥ that are greatly different from those in the usual A-RNA duplexes. as two quadruplexes of r(UG) 4 that are incorporated in the antiparallel fashion. The twist (22°) and the rise (7.3 Å) derived from the base step U1-G2 in the r(UG) 4 of the present crystal structure made it possible to construct a model of an intercalated octaplex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Backbone torsion angles (°) for selected nucleotides in the present structure Boldface type indicates values of torsions ␣ and ␥ that are greatly different from those in the usual A-RNA duplexes. as two quadruplexes of r(UG) 4 that are incorporated in the antiparallel fashion. The twist (22°) and the rise (7.3 Å) derived from the base step U1-G2 in the r(UG) 4 of the present crystal structure made it possible to construct a model of an intercalated octaplex.…”
Section: Resultsmentioning
confidence: 99%
“…as two quadruplexes of r(UG) 4 that are incorporated in the antiparallel fashion. The twist (22°) and the rise (7.3 Å) derived from the base step U1-G2 in the r(UG) 4 of the present crystal structure made it possible to construct a model of an intercalated octaplex. The length of the octaplex can be extended by repeat translating 7.3 Å and rotating 22°of the r(UG) 4 unit along the central axis of octaplex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This antiparallel arrangement of bond dipoles may contribute to the overall electrostatic stabilization. Stacking of exocyclic groups allows the hemiprotonated base pairs to approach to a distance of 3.1 Å [52], much closer than the ~3.4 Å typically found in double-stranded nucleic acids.…”
Section: Structural Implicationsmentioning
confidence: 99%
“…It has been assumed in the past that poly(rC) and poly(dC) form hemiprotonated duplexes [36], but there is no decisive structural proof. About fifteen years ago, NMR [27,50] and later x-ray crystal structures [51,52] showed that dC-rich oligonucleotides adopt a quadruplex form ("i-motif DNA") composed of two intercalated duplexes, each of which consists of CH + ·C base pairs. Crystals of d(CT) 3 grown at neutral pH adopt the quadruplex structure [52], showing that i-motif structures do not require acidic conditions for deoxycytidylates.…”
Section: Structural Implicationsmentioning
confidence: 99%